1D metal-oxalates H2DABCO[M(C2O4)2]·3H2O (M(ii): Co, Mg, Zn): phase transitions and magnetic, dielectric, and phonon properties. Issue 18 (14th April 2020) - Pasińska, Katarzyna; Ciupa, Aneta; Pikul, Adam; Gągor, Anna; Pietraszko, Adam; Ciżman, Agnieszka
Abstract : We report the first example of 1D multiferroic homometallic oxalate, which exhibits ferroelectric phase transition around 219 K and a long-range antiferromagnetic ordering below 4 K. Abstract : The family of 1D hybrid organic–inorganic metal oxalates H2 DABCO[M(C2 O4 )2 ]·3H2 O (where H2 DABCO is diprotonated 1.4-diazoniabicyclo[2.2.2]octane and M(ii ): Co, Mg, Zn) display paraelectric to ferroelectric phase transition between 203 and 217 K, triggered by rearrangement of crystalline water present in the crystal structure. The symmetry decreases from P 21 / n to P 21 . We demonstrate that spontaneous electric polarization arises due to the release of dipolar crystalline water from steric hindrances present in the paraelectric phase. The increased dynamics of water in the ferroelectric phase is preceded by the significant reconstruction of the hydrogen-bond network. Breaking of hydrogen bonds leads to elongation of the metal-oxalate chains resulting in negative thermal expansion in the c -direction as well as distortion of the uncoordinated oxalate ligands. The analysis of IR modes confirms the mechanism of the phase transition while the broadband dielectric spectroscopy reveals significant reduction of activation energy assigned to water rotation at low temperatures. The investigated metal-oxalates act as microporous materials above room temperature, by losing (with heating) and recovering (with cooling) crystalline water. The compounds show switchable dielectric behaviour related to ferroelectric phase transition. Additionally, the Co analogue exhibits spin-canted antiferromagnetic ordering at 7 K and, by extension, is the first multiferroic homometallic 1D oxalato-bridged coordination polymer.